2003
DOI: 10.1007/s11745-003-1145-2
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme‐resistant fractions of beans lowered serum cholesterol and increased sterol excretions and hepatic mRNA levels in rats

Abstract: Feeding rats beans with resistant starch reduces their serum cholesterol concentration; however, the mechanism by which this occurs is not fully understood. We examined the effects of enzyme-resistant fractions of adzuki (Vigna angularis) and tebou (Phaseolus vulgaris, var.) beans on serum cholesterol and hepatic mRNA in rats. Rats were fed a cholesterol-free diet with 50 g of cellulose powder (CP)/kg, 50 g of an enzyme-resistant fraction of adzuki starch (AS)/kg, or 50 g of an enzyme-resistant fraction of teb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 26 publications
2
24
2
2
Order By: Relevance
“…Retrograde starch is a kind of resistant starch that has resistance against amylase, and may act like dietary fiber in the digestive tract. Actually, we have previously reported that resistant starches of beans reduce serum cholesterol and triglyceride (TG) levels in rats (8)(9)(10)(11). It is suggested that the cholesterol-lowering function by the resistant starches of beans was due to cecal fermentation products such as short chain fatty acid (SCFA) and increased fecal steroid excretion (8)(9)(10).…”
mentioning
confidence: 99%
“…Retrograde starch is a kind of resistant starch that has resistance against amylase, and may act like dietary fiber in the digestive tract. Actually, we have previously reported that resistant starches of beans reduce serum cholesterol and triglyceride (TG) levels in rats (8)(9)(10)(11). It is suggested that the cholesterol-lowering function by the resistant starches of beans was due to cecal fermentation products such as short chain fatty acid (SCFA) and increased fecal steroid excretion (8)(9)(10).…”
mentioning
confidence: 99%
“…While no significant difference was found in HDL cholesterol level between the two groups, VLDL + IDL + LDL cholesterol level was significantly lower in the experimental group than in the control group (Table 2). It was therefore suggested, as in the case of the mice given feed supplemented with Adzuki re-sistant starch or enzyme-treated Adzuki resistant starch (Han et al, 2003a(Han et al, , 2003b, that the lower total cholesterol level was attributable to the reduction in VLDL + IDL + LDL cholesterol level. In addition, the AI in the experimental mice was significantly lower than that in the control mice (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Adzuki beans contain dietary fiber, saponins, and polyphenols (Kojima et al, 1989;Kojima et al, 2006aKojima et al, , 2006b). We previously reported that feed containing supplemental resistant starch from Adzuki beans or enzyme-treated Adzuki resistant starch reduced serum cholesterol levels in rats (Han et al, 2003a(Han et al, , 2003b. In this two-week study, the ability of an Adzuki polyphenol (Adzuki-PP) solution to lower serum cholesterol was investigated in mice fed a high-cholesterol diet and administered an Adzuki-PP solution daily via a catheter.…”
Section: Introductionmentioning
confidence: 96%
“…Slowly digestible starch consists of amorphous and raw starches with a type A or C crystalline structure, or type B starch in granule or retrograded form. 4) Resistant starch (RS) cannot be digested in the small intestine and is effective against hyperglycaemia, [5][6][7] hypercholesterolaemia, 8,9) and fat accumulation. 10) RS can be classified into four types.…”
Section: )mentioning
confidence: 99%